Exploring The Dynamics of Insurgency, Belligerency, and Liberation Movements with The Organization of Papua Merdeka - Satriyo Kusumo, Ayub Torry (Magister of Law, Faculty of Law, University of Mataram, 2025)
International Law has developed significantly as there are new subjects in International Law. The rebellion groups that arise from time to time become an important matter to be discussed in the field of International Law, particularly in International Humanitarian Law. The rise of OPM in Indonesia is one of the cases to be studied in international law. This paper aims to analyze the status of OPM in Indonesia from the point of view of International Law. The analysis was elaborated on from the study of insurgency, hostility, and national liberation movements, followed by a legal study to determine the status and position of the OPM. This is a narrative review of literature and the sources are from scientific writings, case reports, and international law literature supported by news and written opinions of legal experts relevant to the subjects discussed. The information from those sources was extracted, classified, and analyzed quantitatively to answer the research question. This study concluded that, despite its history and tactics, the analysis finds that the OPM is not a national liberation movement or belligerent entity under international law. As an internal uprising, OPM must observe Indonesian law. The study emphasizes the need to address the political, economic, and social issues fueling the conflict to find a long-term solution. The Indonesian government should address Papua’s social and economic issues, and Clarifying international law on self-determination is also crucial to avoid misunderstandings that could favors separatist aspirations